Creation of bread spring wheat breeding material with wheat-rye translocations - С. О. Хоменко; В. А. Власенко; Т. В. Чугункова; І. В. Федоренко; Д. Ю. Березовський; Т. А. Данюк (Plant varieties studying and protection, 2019)
Purpose. Creation of bread spring wheat varieties using domestic and foreign varieties as carriers of wheat-rye translocation. Меthods. Field, laboratory, statistical. Results. The creation of varieties with wheat-rye translocation 1AL.1RS is the perspective direction of breeding, which allows to significantly improve the gene pool of bread spring wheat. The paper covers outputs of long-term breeding studies conducted at the V. M. Remeslo Myronivka Institute of Wheat of the National Academy of Agrarian Sciences of Ukraine (MIW) for obtaining bread wheat varieties with wheat-rye translocation 1AL.1RS. As the initial breeding material varieties and lines of domestic and foreign breeding were used, in particular, the ‘TAM 107’ variety (USA) with wheat-rye translocation 1AL.1RS. During realization of the scientific breeding program, the bread winter wheat variety ‘Ekspromt’ (1AL.1RS), as well as the bread spring wheat varieties ‘Struna myronivska’ (1AL.1RS) and ‘MІP Solomіia’ (1AL.1RS) have been created. As evidenced by the analysis of the spectrum of storage proteins, the varieties ‘Struna myronivska’ and ‘MIP Solomiіa’ contain wheat-rye translocation 1AL.1RS in their genomes. The variety ‘MIP Solomiіa’ inherited it from the variety of bread spring wheat ‘Struna myronivska’. The bread spring wheat new variety ‘MІP Solomiia’ is characterized by high yielding capacity, adaptability, resistance to powdery mildew, fusarium head blight, common bunt and high indices of grain quality. Conclusions. By long-term single crossing foreign varieties and domestic breeding material when using the pedigree method, bread wheat varieties with wheat-rye translocation 1AL.1RS have been created. The bread spring wheat variety ‘MІP Solomiia’ submitted for the State Variety Testing in 2017, is characterized by high yielding capacity, lodging resistance, low incidence of fungal diseases, resistance to common bunt, adaptability. The presence of wheat-rye translocation in spring wheats varieties of Myronivka breeding ‘Struna myronivska’ and ‘MІP Solomіia’ has been confirmed by analyzing the spectrum of storage proteins during polyacrylamide gel electrophoresis. Мета. Створити сорти пшениці м’якої ярої за використання вітчизняних та іноземних сортів, носіїв пшенично-житньої транслокації (ПЖТ). Методи. Польові, лабораторні, статистичні. Результати. Перспективним напрямом селекції, що дає змогу суттєво поліпшити генофонд пшениці м’якої ярої, є створення сортів із ПЖТ 1АL.1RS. Представлено опис багаторічних селекційних досліджень, проведених у Миронівському інституті пшениці імені В. М. Ремесла НААН України (МІП), щодо одержання сортів пшениці м’якої з ПЖТ 1АL.1RS. Як вихідний селекційний матеріал використовували сорти й лінії вітчизняної та іноземної селекції, зокрема сорт ‘ТАМ 107’ (США) із ПЖТ 1АL.1RS. У процесі виконання наукової селекційної програми створено сорти пшениці м’якої озимої ‘Експромт’ (1АL.1RS), м’якої ярої ‘Струна миронівська’ (1АL.1RS) та ‘МІП Соломія’ (1АL.1RS). Сорти ‘Струна миронівська’ та ‘МІП Соломія’, згідно з результатами аналізу спектра запасних білків, містять у своїх геномах ПЖТ 1АL.1RS. ‘МІП Соломія’ успадкував її від сорту пшениці м’якої ярої ‘Струна миронівська’. Новий сорт пшениці м’якої ярої ‘МІП Соломія’ характеризується високою врожайністю, адаптивністю, стійкістю проти борошнистої роси, фузаріозу колоса, твердої сажки, високими показниками якості зерна. Висновки. Шляхом багаторічних простих парних схрещувань іноземних сортів та вітчизняного селекційного матеріалу з використанням методу педігрі створено сорти пшениці м’якої з ПЖТ 1АL.1RS. Сорт пшениці м’якої ярої ‘МІП Соломія’, переданий у 2017 р. до Державного сортовипробування, характеризується високою врожайністю, стійкістю до вилягання, низьким відсотком ураженості грибними хворобами, стійкістю проти твердої сажки, адаптивністю. Наявність пшенично-житньої транслокації в сортів ярої пшениці миронівської селекції ‘Струна миронівська’ та ‘МІП Соломія’ підтверджено за допомогою аналізу спектра запасних білків за електрофорезу в поліакріламідному гелі.